A formação científica e humanística de Antonio Francisco de Paula Souza, o fundador da Escola Politécnica de São Paulo - Padilha, Rodrigo Bastos (2009)
The central subject of this master dissertation is the scientific and humanistic education of Antonio Francisco de Paula Souza (1843-1917), founder of the S. Paulo Engineering Polytechnic School and its first director, during 14 years. The master dissertation scrutinizes the following aspects: his primary studies in Brazil, his secondary studies in Dresden (Germany), his engineering studies in Switzerland (Zurich) and in Germany (Karlsruhe), the family of his wife (Herwegh family), his return to Brazil, his experience in the United States of America, his involvement in the republican convention of Itu, his careers as an engineer and as a politician, his dispute with Euclides da Cunha and the foundation of the S. Paulo Engineering Polytechnic School. During his stay in Zurich he registered himself in the courses of engineering at the Engineering Polytechnic School (ETH) and of philosophy at the University of Zurich, simultaneously. This dual registration created him problems with the ETH superiors. Analyses of his school grades and the writing of his final examinations, at the Karlsruhe Polytechnic, showed a solid academic formation and accentuated interest in railroad construction and in water dams. These have been exactly the emphasis of his career acting as an engineer. The engineering education model introduced in the S. Paulo Polytechnic also keeps narrow relation with the type of engineering education practiced at the time in Zurich and in Karlsruhe. The proposal of the creation of the S. Paulo Engineering Polytechnic School followed the model of the Swiss and German engineering schools, focusing the education towards applied sciences, arts and to industries, as opposed to the positivistic model adopted in Rio de Janeiro, defended by Euclides da Cunha